Tinjauan Kritis Tentang Pemerintah dan Kewenangan Pemerintah Menurut Hukum Administrasi Negara - Tri Widodo W. Utomo (Universitas Islam Indonesia, 2005)
During New Order period, government was the most powerful institution with 'unlimited' authorities and having less control from other state institutions. Consequently, it tended to promulgate many policies overwhelming its power. Only after the 2004 Election, the new regime has declared its pledge to reform the bureaucracy. Bureaucratic reform alone Is Inadequate, however. It has to be accompanied by law reform, particularly In the field of constitutional / public administration law (hukum administrasi negara). In that sense, this paper tries to elaborate two basic dimensions of constitutional law. I.e. government dimension and authority dimension. Those two dimensions consist certain facets that contribute to violation of law as practiced in the past. Hence, to prevent the appearance of similar case in the future, all facets of government (bureaucracy) and authority should be carefully scrutinized and simultaneously recovered.